Isolated word recognition system development - Tamulevičius, Gintautas; Lipeika, Antanas (Lietuvos matematikos rinkinys, 2003)
Isolated word recognition system, based on dynamic time warping, was developed. Speech patterns are represented by LPC, cepstral and weighted cepstral coefficients. Two endpoint detection, two speech input and two pattern training methods are implemented in the system. The system performance was investigated.